ANALISIS EFISIENSI PEMASARAN BERAS ORGANIK DI DESA SUMBERNGEPOH KECAMATAN LAWANG KABUPATEN MALANG - Nadiya Khoirul Arifah (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
ABSTRACT The objectives of this study include: (1) Observe the marketing channels of organic rice, (2) Knowing the amount of margin and share on the marketing channels of organic rice, (3) Analyzing the marketing efficiency of organic rice This study was determined intentionally in Sumberngepoh Village, Lawang District, Malang Regency , based on calculations in the area, it is the center of organic rice in Malang Regency. Farmer samples were determined by 30 people, using simple random sampling method, while marketing institutions were determined based on information on the flow of goods from farmers, with the snow ball sampling method. The results showed that there were 2 marketing channels, namely Channel I: Farmers of GAPOKTAN Consumer. Channel II: GAPOKTAN Farmers Large Wholesalers of Consumer Retailers. In channel I the total margin is Rp. 2,495 / kg and the share of farmers is 81.4%, and in channel II the total margin is Rp. 8,091.92 / kg and farmer's share of 57.5%. The results of the analysis of marketing efficiency with the approach to price efficiency analysis at the marketing agency of organic rice in Sumberngepoh Village, Lawang Subdistrict, Malang Regency are said to be efficient on channel I, because it can be seen from the small marketing margin and large farmer share. Whereas on channel II it cannot be said to be efficient because it has a large margin and small share of farmers. While the analysis of operational efficiency in the transportation and labor function has been achieved in each marketing channel. This is because the average transport capacity in each institution is in accordance with its normal transport capacity. Keywords: marketing efficiency, marketing channels